iAlerto: A Web and Mobile Alert System for Pasig City Disaster Risk Reduction Management Office (PCDRRMO) with mobile GPS service integration - Goh, Marie Luvett I.; Manahan, Vanessa Aila Mae M.; Mangalus, Clyde Justine U.; Carreon, Richard Jerard V.; Ong, Charles Cedric T.; Vicente, Heintjie N. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The study aimed to develop a web and mobile application to improve the incident or emergency reporting of the residents in Pasig City and to better support the disaster response of PCDRRMO. Method - The study employed the scrum methodology in software development. Android Studio was used to develop the mobile application, while Code Igniter was used for the web application. PHP was used as a backend scripting language together with MySQL database and XAMPP web server for testing. The functionality of the system was evaluated by 20 IT professionals and 20 residents and DRRMO employees of Pasig City using the ISO-9126 functionality sub-characteristics criteria. Results - The PCDRMMO was able to collect information from Pasig City residents and barangays that would be useful for decision-making and generating reports. The web application enables the management of users' profiles, barangay's evacuation centers, incident reports, sends alerts or announcements and generates reports. Also, the mobile applications utilize GPS mobile service to determine the exact location of the incident. In the software evaluation, the overall system proves to be functional as perceived by the respondents as manifested by the mean rating of 4.48. Conclusion - The design of the developed multi-platform applications was found feasible to improve the incident or emergency reporting of the residents in Pasig through the use of a mobile app. The system proves to be functionally acceptable as perceived by the respondents, which implies that the design framework of the study can be feasibly implemented. Recommendations - An SMS module must be integrated into the system to allow people with no Internet connection to receive announcements from PCDRRMO before, during, or after a disaster. Survey response feature that will solicit feedback from people by sending them a multiple-choice survey to perform wellness checks during critical events.